From collaborative practices to the classroom as a network laboratory - Espinosa Pérez, Enrique; Pascual García, Manuel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
In the last 25 years, a number of radical transformations have taken place in the world and in architecture. These have put in crisis not only the professional paradigm of our discipline, but also, consequently, its educational model. Internet, the real estate and educational bubbles, and a recession and transformation of the economy in Europe within a hyperconnected world, have favored the emergence of other models of professional exercise which have anticipated potential revolutions in the teaching-learning duo.In the Spanish context, the emergence of a collective architecture scenario between 2001 and 2010 is relevant. Within these practices, echoes have been detected with global phenomena in the spheres of innovation and open culture; at the same time, these practices imply per se contexts where collaborative production and learning take place in a singular and reciprocal way. This article traces possible methodological transfers between these collective environments and a new university classroom model that enhances teamwork. The class understood as a community with connections between each other and to contemporary reality and university experience as a laboratory. The student is protagonist accompanied within a network learning experience.
Keywords: Learning; Collaboration; Peertopeer; Experience; Network; Tactic